Metastatic breast cancer to the rectum: A case report with emphasis on MRI features. Issue 17 (April 2017) - Lau, Li Ching; Wee, Bernard; Wang, Shi; Thian, Yee Liang
Abstract: Rationale: Less than 1% of breast carcinomas metastasize to the gastrointestinal tract. The diagnosis is frequently not recognized especially when the history of breast carcinoma is remote. Patient concerns: A 61-year-old female with a remote history of breast carcinoma presented with a 3-month history of change in bowel habits. Colonoscopy showed a circumferential rectal mass with initial impression of primary rectal cancer. MRI of the rectum showed findings that are atypical for primary rectal cancer. Diagnoses: Deep biopsy of the rectal mass confirmed lobular breast carcinoma metastasis to the rectum. Intervention and outcomes: The patient was treated with radiotherapy and hormonal therapy. She is symptomatically well 2 years after presentation and remains on hormonal therapy. Lessons: Lobular breast cancer which metastasizes to the rectum can mimic primary rectal cancer clinically. The unique MRI features described in our case when present with a concordant history of lobular breast carcinoma should alert the radiologist to the possibility of this diagnosis which has important treatment implications.